Pengaruh Hedonic Shopping Motivation dan Sales Promotion Terhadap Impulsive Buying Melalui Positive Emotion sebagai Variabel Mediasi Pada Pengguna Tiktok Shop (Studi Kasus Pada Generasi Z Di Jakarta) - Mohamad Rohadi; Setyo Ferry Wibowo; Terrylina Arvinta Monoarfa (Teewan Journal Solutions, 2025)
The purpose of this research is to determine the positive and significant influence of hedonic shopping motivation and sales promotion on impulsive buying in generation z tiktok shop users in Jakarta, with positive emotion as a mediating variable. Data collection was carried out through a Google Form questionnaire using a 5-point Likert scale. The research sample was 300 respondents who had made impulsive purchases at tiktok shop. Data analysis included validity and reliability tests, as well as hypothesis testing using AMOS software version 24. The results showed that hedonic shopping motivation and sales promotion had a positive and significant effect on positive emotion. Furthermore, hedonic shopping motivation, sales promotion and positive emotion had a significant effect on impulsive buying. Positive emotion proved to be a significant mediator between hedonic shopping motivation and sales promotion with impulsive buying.